Dwarf shrubs may mitigate the negative effects of climate change on spiders by moderating microclimate - Gallé, Róbert; Gallé-Szpisjak, Nikolett; Batáry, Péter (Basic and applied ecology, 2024)
•Dwarf shrubs cooler and moister than the surrounding grassland.•Therefore, dwarf shrubs buffer microclimatic extremities.•Forests and edges had a higher spider richness than grasslands and dwarf shrubs.•We found a different community composition of spiders in the four microhabitats. Climate change negatively affects arthropod biodiversity worldwide. Mitigating the resulting arthropod decline is a great challenge. Dwarf shrubs in open areas might buffer microclimatic extremities by reducing the solar radiation reaching the ground and weakening air circulation near the soil surface. Forest steppes are mosaics of forests and grasslands covering a vast area in Eurasia. This heterogeneous ecosystem offers the opportunity to study the effect of small habitat features, i.e. dwarf shrubs, in dry grasslands and compare the fauna of rosemary-leaved willow (Salix rosmarinifolia) shrubs with forest patch interiors, open grasslands and their edges. We hypothesized that the dwarf shrub microhabitat has a wetter and cooler microclimate than open grassland and a different spider community composition than other forest-steppe microhabitats. We recorded microclimatic parameters with data loggers, measured soil moisture with TDR and collected ground-dwelling spiders with pitfall traps. We detected the highest soil moisture (6.26 ± 1.21%, mean ± 95% confidence interval) and air humidity (80.19 ± 3.19%) in forests and the lowest in grasslands (4.36 ± 0.65%; 66.59 ± 2.53%, respectively). The warmest microhabitats were grasslands (23.23 ± 0.51°C), whereas the coolest microhabitats were forests (18.92 ± 0.41°C). The distinct microclimate of dwarf shrubs was cooler (21.46 ± 0.41°C) and moister (5.43 ± 0.53%) than the surrounding semi-desert like grassland. Furthermore, we found a different spider community composition and trait state composition of spiders in forests, edges, grasslands and dwarf shrub microhabitats. Forests (9.90 ± 0.95) and edges (11.44 ± 1.27) hosted a higher species richness than grasslands (7.08 ± 4.27) and dwarf shrubs (5.09 ± 1.33). We collected larger spiders on the edges than in dwarf shrub microhabitats. The dwarf shrubs hosted a different microclimate and spider community composition from the grassland. Climate change in the forest-steppe region is assumed to be driven by a combination of warming and drying. In the coming decades, drought frequency and severity are predicted to increase. Woody vegetation, even dwarf shrubs, creates a thermal and moisture heterogeneity that might aid arthropods in buffering macroclimatic warming through behavioural thermoregulation. Therefore, their presence on grasslands can benefit the conservation of specialised grassland arthropods.